2015
DOI: 10.1016/j.ijcha.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against basement membrane collagen type IV are associated with myocardial infarction

Abstract: BackgroundCollagen type IV is the major constituent of basement membranes underlying endothelial cells and is important for endothelial cell attachment and function. Autoantibodies against native collagen type IV have been found in various autoimmune diseases. Oxidation of LDL in the vascular wall results in the formation of reactive aldehydes, which could modify surrounding matrix proteins. Like oxidized LDL, these modified matrix proteins are likely to induce immune responses. We examined whether autoantibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…In the present study, the association between high levels of IgG antibodies against MDA-collagen type IV in plasma and increased risk of development of MI was independent of cardiovascular disease risk factors. In a previous study, we showed that IgG antibodies against MDA-collagen type IV was decreased in post-MI patients, although this difference was not independent of traditional risk factors [42]. We cannot exclude the possibility that the increased levels of IgG antibodies against MDAcollagen type IV in patients who later developed MI in the present study might reflect a defence mechanism against atherosclerosis rather than a proatherogenic role of these antibodies.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In the present study, the association between high levels of IgG antibodies against MDA-collagen type IV in plasma and increased risk of development of MI was independent of cardiovascular disease risk factors. In a previous study, we showed that IgG antibodies against MDA-collagen type IV was decreased in post-MI patients, although this difference was not independent of traditional risk factors [42]. We cannot exclude the possibility that the increased levels of IgG antibodies against MDAcollagen type IV in patients who later developed MI in the present study might reflect a defence mechanism against atherosclerosis rather than a proatherogenic role of these antibodies.…”
Section: Discussioncontrasting
confidence: 64%
“…In a previous study, we showed that IgG antibodies against MDA-collagen type IV was decreased in post-MI patients, although this difference was not independent of traditional risk factors [42]. In a previous study, we showed that IgG antibodies against MDA-collagen type IV was decreased in post-MI patients, although this difference was not independent of traditional risk factors [42].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The lack of effect on atherosclerosis by immunization with collagen type IV α1α2 peptides suggests that autoantibodies against collagen type IV, previously associated with cardiovascular disease in humans 8,29 , do not play a pathogenic role. In a previous study immunization against aldehyde-modified laminin, another extracellular matrix protein present in basement proteins, resulted in increased atherosclerosis in apoE −/− mice 2 .…”
Section: Discussionmentioning
confidence: 97%
“…Collagen type IV is one of the major components of basement membranes underlying endothelial cells and surrounding smooth muscle cells 28 . Observational studies have identified associations between autoantibodies against collagen type IV and risk for development of cardiovascular disease 8,29 . In the present paper we investigated the effect on an immune response against the basement membrane collagen type IV on atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 99%